A systematic scoping review of mentoring support on professional identity formation - Lalit Kumar Radha Krishna; Hannah Yi Fang Kwok; Nila Ravindran; Xuan Yu Tan; Jasper Soh; Darius Wei Jun Wan; Varsha Rajalingam; Jun Kiat Lua; Elizabeth Yong Mei Leong; Tiat Yan Low; Aiden Wei-Jun Chan; Chong Jin Nicholas Lim; et al. (BMC Medical Education)
Abstract Background Mentoring’s success in nurturing professional identity formation (PIF) has been attributed to its ability to build personalised and enduring mentoring relationships. However, beyond functioning as communities of practice (CoPs) supporting socialisation processes, how mentoring integrates programme values and instils a shared identity amongst mentees remains unclear. The need for personalised guidance and timely attention to a mentee’s unique needs in evolving mentoring relationships point to the critical role of support mechanisms (‘mentoring support’). We conducted a systematic scoping review (SSR) studying “What is known about mentoring support’s role in nurturing PIF?”. Methods Adopting PRISMA-ScR guidelines, this SSR was guided by the Systematic Evidence-Based Approach (SEBA). Independent searches were carried out on publications featured between 1st January 2000 and 30th June 2023 in PubMed, Embase, ERIC and Scopus databases. The Split Approach saw concurrent, independent thematic and content analyses of the included articles. The Jigsaw Perspective combined complementary themes and categories, creating broader themes/categories. The subsequent Funnelling Process formed key domains that platformed the synthesis of the discussion. Results Two thousand three hundred forty-one abstracts were reviewed, 323 full-text articles were appraised and 151 articles were included and analysed. The key domains identified were (1) definitions and roles; (2) personalisation; (3) shepherding; and (4) PIF. Conclusion The success of mentoring in PIF lies in its ability to blend role modelling, supervision, mentoring, coaching and teaching, with self-care, guided reflection, apprenticeship and assessment to meet the individual needs of the mentee and their changing circumstances. Blending the contents of the mentoring umbrella emphasises the critical role of the mentor and host organisation in supporting mentor training, communications, support and assessment mechanisms. Mentee engagement and its active role in support measures complement the CoP-like mentoring programme’s use of blending mentoring support to advance the socialisation process. These insights reflect a complex interactive process scaffolding the development of mentoring relationships and PIF. The effect of the mentoring umbrella on clinical practice requires further study.